Antibacterial Activity and Cytotoxicity of Immobilized Glucosamine/Chondroitin Sulfate on Polylactic Acid Films - Karakurt, Ilkay; Ozaltin, Kadir; Vesela, Daniela; Lehocky, Marian; Humpolíček, Petr; Mozetič, Miran (Polymers, 2019)
Polylactic acid (PLA) is one of the most produced polymeric materials, due to its exceptional chemical and mechanical properties. Some of them, such as biodegradability and biocompatibility, make them attractive for biomedical applications. Conversely, the major drawback of PLA in the biomedical field is their vulnerability to bacterial contamination. This study focuses on the immobilization of saccharides onto the PLA surface by a multistep approach, with the aim of providing antibacterial features and evaluting the synergistic effect of these saccharides. In this approach, after poly (acrylic acid) (PAA) brushes attached non-covalently to the PLA surface via plasma post-irradiation grafting technique, immobilization of glucosamine (GlcN) and chondroitin sulfate (ChS) to the PAA brushes was carried out. To understand the changes in surface properties, such as chemical composition, surface topography and hydrophilicity, the untreated and treated PLA films were analyzed using various characterization techniques (contact angle, scanning electron microscopy, X-ray photoelectron spectroscopy). In vitro cytotoxicity assays were investigated by the methyl tetrazolium test. The antibacterial activity of the PLA samples was tested against Escherichia coli and Staphylococcus aureus bacteria strains. Plasma-treated films immobilized with ChS and GlcN, separately and in combination, demonstrated bactericidal effect against the both bacteria strains and also the results revealed that the combination has no synergistic effect on antibacterial action.
Keywords: count-plate method; surface modification; plasma treatment; saccharide immobilization; cytotoxicity; antibacterial activity; chondroitin sulfate